Legal implications of the arbitration agreement in terms of subject matter - Belabed, Toufik (Journal of Human Sciences, 2020)
The arbitration agreement has two effects, one positive and the other negative: The negative impact is the commitment of the parties to refrain from going to court to rule on the dispute being arbitration, commitment resulting in the elimination of the jurisdictional consideration. The positive effect is that the parties to the approved arbitral tribunal are allowed to rule in accordance with the conditions provided for by the parties’ agreement and the provisions of the arbitration law. If these effects result from the arbitration agreement, they are bound by the validity of this agreement and their survival depends on the survival of the latter.